Penerapan Metode Pembelajaran Lucky Day! If You Lucky sebagai Upaya Meningkatkan Keaktifan Siswa dalam Pembelajaran Sejarah Kelas XI IPS 1 - Rahmawati, Duni; Winarti, Murdiyah (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
The research aims to describe applying the Lucky Day learning method, If You Lucky, in learning history. The research uses the Class Action Research method with the Kemmis and Taggart model research design, which consists of planning, implementation, action, observation, and reflection levels. The research results show increased student activity in each cycle after applying the Lucky Day method! If You Lucky in Learning History. The improvement occurred in several indicators, namely exchanging answers between large groups, checking the correctness of answers, and exchanging points. Application of the Lucky Day method! If You Lucky can be an alternative to increase student activity in learning history. Schools can optimize the library as a means of learning for students so that they have many reference sources.